Proteínas diferencialmente abundantes entre isolados de Leishmania (Viannia) braziliensis caracterizados como agentes de lesões atípicas e típicas - Barbara Beiral Esteves Santana (2023)
Leishmania (Viannia) braziliensis is the main etiologic agent of American cutaneous leishmaniasis, which presents various of clinical manifestations, from typical skin lesions to involvement of the nasal and oral mucous, known as mucocutaneous leishmaniasis. In addition, this species can cause atypical lesions such as papules, verrucous and keloid lesions, and crusty and ulcerated plaques. Cases of non-ulcerated atypical cutaneous leishmaniasis caused by L. braziliensis have been reported in various regions of the world, including the Xacriaba indigenous reserve in São João das Missões/Minas Gerais, Brazil. L. braziliensis is characterized by variable infectivity, virulence, and therapeutic response, and there is no consensus on the factors involved in cases of atypical clinical manifestations. In the present study, proteins that show differential abundance in two strains of L. braziliensis isolated from patients with atypical lesions (LbAL) compared to four strains isolated from patients with typical lesions (LbTL) were identified using a quantitative proteomic approach based on tandem mass tag (TMT) labeling and mass spectrometry (MS). A total of 532 (p<0.05) differentially abundant proteins were found in strains with atypical lesions compared to strains with typical lesions. Gene ontology (GO) enrichment analysis showed that the upregulated proteins were associated with molecular functions involving oxidoreductase activity and biological processes such as cellular nitrogen compound biosynthetic process and peptide metabolic process. Downregulated proteins were associated with serine/threonine protein kinase activities and biological processes such as carbon fixation in prokaryotes and valine, leucine, and isoleucine degradation. The positive regulation of antioxidant proteins present in the glutathione pathway was confirmed by the peroxidase activity test, since hydrogen peroxide consumption in the LbAL group was 3.01 times higher than in the LbTL group (p<0.001). In addition to proteins associated with higher peroxidase activity (tryparedoxin peroxidase), methionine sulfoxide reductase-like) upregulated proteins in strains causing atypical lesions included those that may confer greater survival within macrophages (trypanothione reductase), proteins that influence the early stages of mammalian host infection (ISP), and proteins related to antimony resistance (tryparedoxin peroxidase). Our findings contribute to the characterization of these intriguing strains of L. braziliensis and provide a new perspective on cases of atypical cutaneous leishmaniasis that have been associated with therapeutic failures